Association between 25-Hydroxyvitamin D and Mental-Emotional Status in Children during Their First 1000 Days of Life - Maryam Rusli; Susi Susanah; Sri Endah Rahayuningsih; Nelly Amalia Risan; Diah Asri Wulandari; Meita Dhamayanti (Faculty of Medicine, Universitas Padjadjaran, 2022)
Vitamin D receptors are widely expressed in brain tissue, including in the limbic system that plays a role in children's mental and emotional development. This study aimed to analyze the relationship between 25-(OH)-D level and children's mental-emotional development during their first 1000 days of life. A cross-sectional study was conducted on children aged ≤2 years old in Waled and Sukabumi regions using secondary data from previous cohort investigations entitled